PENGEMBANGAN LKPD BERBASIS PBL: STUDI VALIDITAS DAN PRAKTIKALITAS UNTUK KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN MATEMATIKA SD - Damayanti, Lisa; Nurhanurawati; Pratitis, Wahyu Titi; Rohman, Fatkhur; Kurniawan, Ikhsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a Problem Based Learning (PBL)-based Student Worksheet (LKPD) that is both valid and practical to enhance the critical thinking skills of fifth-grade elementary school students in the topic of solid geometry. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of five phases: analysis, design, development, implementation, and evaluation. Validation was conducted by subject matter and language experts, resulting in an average score of 0.858, categorized as highly valid. A practicality test was carried out using questionnaires for students and teachers, showing a practicality level of 92%, classified as highly practical. Student responses indicated that the developed LKPD features an attractive design, is easy to understand, and effectively facilitates critical thinking activities and mathematical problem solving. Therefore, the PBL-based LKPD is deemed feasible for use as an innovative and effective learning medium to support the improvement of mathematics instruction quality in elementary schools.